Expediente (Revista do Tribunal Regional Federal da 3ª Região, 2022)
DIRETOR DA REVISTA:Desembargador Federal Souza RibeiroASSESSORA:Simone de Alcantara SavazzoniEQUIPE:Renata Bataglia GarciaSilvio Pires de QueirozCAPA:Paulo Polimeno
Keywords: Expediente; v. 33; n. 152; jan./mar. 2022